Hölder metric subregularity for multifunctions in type Banach spaces. (1st November 2016) - Zhang, Binbin; Ng, Kung-Fu; Zheng, Xi Yin; He, Qinghai
Abstract : Using the Borwein–Preiss variational principle and in terms of the proximal coderivative, we provide a new type of sufficient conditions for the Hölder metric subregularity and Hölder error bounds in a class of smooth Banach spaces. As an application, new characterizations for the tilt stability of Hölder minimizers are established.